Application of Augmented Reality Technology in Android-based Creative and Interactive Learning Simulation - Algantara, Fahrezi Daffa; Aji, Adam Sekti (Kirana Publisher (KNPub), 2024)
Creative learning media is media made by teachers tailored to the subject matter/subject matter, theme/subtheme so that it really suits the material and the needs of students. Interactive learning media can encourage students to learn independently, resulting in student-centred learning. As a result, the utilisation of technology to create effective learning media is necessary. Virtual technology accurately represents real objects when providing information. Augmented Reality is one example of virtual technology. Augmented reality is a concept that combines digital data into the virtual world and displays it in real time. Augmented reality uses the use of objects as markers to display 3-dimensional images, videos, audio, text, and visuals, as well as virtual 3-dimensional tools and practicum materials and simulation videos in learning. Since 3-dimensional objects, text, images, video, and audio can be displayed to students in real time, learning media using augmented reality technology with markerbased tracking method can easily improve student understanding. This research method uses quantitative research method based on literature study and DDD-E development method. At the design stage the author uses a structured design method, namely the Unified Modelling Language (UML) which includes Use Case, and activity diagrams, navigation structures and storyboards. This application is designed with Unity 3D software using the Vuforia sdk. So the results of the above design are implemented into an application called Pustaka Nusantara Application which can display 3-dimensional objects to support creative learning media and realise an interactive learning system.